Strategi Pengembangan Pasar Wisata Pendidikan Di Renzo Edupark Sukabumi - Dhian Tyas Untari; Erik Saut H Hutahaean; Fata Nidaul Khasanah; Adi Fahrudin; Tiara Anggita Perdini; Erwan Mulyanto (Jurnal Kajian Ilmiah, 2023)
One of the educational tourist destinations in Sukabumi is Renzo Edupark. Renzo Edupark is in Cibadak Sukabumi, in the Dynamix Forest area or used to be called Holcim Education Forest. In its development, developing a marketing strategy is very important to maintain the sustainability of Renzo Edupark as a leading educational tourism destination in Sukabumi. This type of research is qualitative descriptive research. The object of this research is Renzo Edupark which is located in Cibadak District, Sukabumi. Data collection techniques were carried out through observation and interviews. The type of data used is primary data in the form of interviews with management and consumers. Apart from that, this research also uses secondary data obtained from literature studies through journals and books. The data analysis technique used in this research is the IFAS (Internal Strategic Factors Analysis Summary) dan EFAS (External Strategic Factors Analysis Summary) matrices, grand matrices and SWOT analysis (Strength, Weakness, Opportinity, Threats).